Building a synergy between mentors’ field practices and teacher-trainees’ performance in student teaching - Gail G. Gumilet; Bonimar T. Afalla; Sanny J. Dangis (International Journal of Evaluation and Research in Education (IJERE), 2021)
The gradual change from the position of a teacher-trainee to the role of a teacher depends on effective teamwork between educational institutions and the wider education community. Hence, this study ascertained the relationship between the field practices of college deans, supervising instructors, school principals, and teachers and the teaching performance of teacher-trainees. A descriptive-correlational study was employed in this study. A rating scale was used to collect data from the mentors and teacher-trainees who served as respondents. Descriptive statistics such as frequency counts, percentages, and weighted means were employed to describe the levels of mentors’ field practices and teaching performance of teacher-trainees. To establish a significant relationship between the variables, the Spearman rank-order of correlation coefficient was used. Results of the study show that when the deans, supervising instructors, school principals and cooperating teachers manifest an exceptional level of field practices in student teaching, it follows that all the dimensions of field practices are highly practiced. Further, when the teacher-trainees exhibit an exemplary teaching performance, all other dimensions of student teaching are also found to be remarkable. Finally, an outstanding field practice in the student teaching shows minor or slight influence in the outstanding teaching performance of teacher-trainees.